Determination of the diagnostic values of asymmetric dimethylarginine as an indicator for evaluation of the endothelial dysfunction in patients with rheumatoid arthritis - Spasovski, Dejan; Latifi, Arif; Osmani, Bashkim; Krstevska balkanov, Svetlana; Kafedziska, Irena; Slaninka-Micevska, Maja; Dejanova, Beti; Alabakovska Sonja; Balkanov, Trajan (Hindawi Limited, 2013)
Introduction. To compare the diagnostic values of laboratory variables, to present evaluations of the diagnostic test for asymmetric dimethyl arginine (ADMA), rheumatoid factor (RF), C-reactive protein (CRP), and DAS28 index, and to define the effect of untreated rheumatoid arthritis on endothelial function. In order to determine whether ADMA changes depending on the disease evolution, ADMA was used as an indicator for endothelial dysfunction. Methods. Using an ELISA technology of DLD-Diagnostika-GMBH for the detection of ADMA, the samples of serum and urine have been examined in 70 participants (35 RA who were not treated, 35 healthy controls). RF was defined with the test for agglutination (Latex RF test) in the same participants. Results. Out of 35 examined patients with RA, RF appeared in 17 patients (sensitivity of the test, 51.42%). In 20 of the 35 examined patients with RA, we found the presence of ADMA (sensitivity of the test, 57.14%). Anti-CCP antibody was present in 24 examined patients with RA (sensitivity of the test, 68.57%). Conclusion. ADMA has equal or very similar sensitivity and specificity to RF in untreated RA (sensitivity of 57.14% versus 48.57%, specificity of 88.57% versus 91.42%) in the detection of asymptomatic endothelial dysfunction in untreated RA.